On the bulk glass formation in the ternary Pd-Ni-S system. (1st October 2018) - Kuball, Alexander; Bochtler, Benedikt; Gross, Oliver; Pacheco, Victor; Stolpe, Moritz; Hechler, Simon; Busch, Ralf
Abstract: We report on the formation of bulk metallic glasses in the ternary Pd-Ni-S system. In a large compositional range, glass formation is observed by copper mold casting with a glass forming ability of up to 2 mm in diameter for the composition Pd37 Ni37 S26 . The best compromise of thermal stability upon heating from the as-cast state and glass forming ability was found for Pd31 Ni42 S27, having a critical diameter of 1.5 mm and an extension of the supercooled liquid region of 27.2 K (ΔTx = Tx – Tg ). Differential scanning calorimetry and X-ray diffraction experiments were conducted in order to study the influence of the composition on the glass forming ability and thermal stability. The primary precipitating crystalline phases Ni3 S2 and Pd4 S are identified by in-situ high energy synchrotron X-ray scattering experiments upon heating from the glassy state as well as upon cooling from the equilibrium liquid. Finally, the origin of the bulk glass formation in this novel system is discussed regarding thermodynamics and kinetics and compared to current models for the prediction of the glass forming ability. Furthermore, the mechanical properties are investigated and discussed with respect to the rather fragile kinetic behavior. All in all, we gain new insights into the process of glass formation in this novel alloying system and give conclusions about the determining contributions for the glass forming ability and glass forming range. Graphical abstract: Image 1